Small Cell Prostate Carcinoma: A Case Report and Review of the Literature - Abdullah Demirtaş; Nurettin Şahin; Figen Öztürk; Emre Can Akınsal; Türev Demirtaş; Oguz Ekmekçioğlu; Atila Tatlışen (Case Reports in Urology)
Small cell prostate cancer constitutes less than 1% of all prostate cancers and has a poor prognosis. A 60-year-old male patient presented with dysuria, pollakiuria, and nocturia of about 1-year duration.The total PSA level at admission was 47.50 ng/mL. The prostate needle biopsy result was reported as adenocarcinoma Gleason 5 + 3. The patient underwent transurethral prostate resection (TUR-P) and bilateral orchiectomy. The TUR-P pathology result was consistent with small cell neuroendocrine carcinoma. He was offered systemic chemotherapy but refused it. Examinations and tests at the third postoperative month showed diffuse liver metastasis and vertebral bone metastasis. He died at the 6 months after surgery.